2017
DOI: 10.1016/j.chemosphere.2017.03.122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filtration mode and backwash water on hydraulically irreversible fouling of ultrafiltration membrane

Abstract: To investigate the effect of filtration mode and backwash water on ultrafiltration (UF) membrane performance, total fouling index (TFI) and hydraulic irreversible fouling index (HIFI) for constant pressure (CP) filtration and constant flux (CF) filtration were compared. Kaolin, humic acid (HA) and sodium alginate (SA) solutions were used as feed solutions, and then the fouled membranes were backwashed with UF permeate or ultrapure water. Results showed that when the kaolin solution was filtrated, the filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Research findings indicate that both pore narrowing and pore blockage initiate the buildup of a cake/gel layer on the membrane surface [61,62,63,64,65]. Pore narrowing and pore blockage are considered irreversible and a formation of gel/cake layer primarily reversible [66,67]. For example, Zhang et al 190 [68] found that the absorption of low and high MW hydrophilic compounds led to irreversible membrane fouling; due to their hydrophilicity, these fractions are not restricted from entering the membrane pore.…”
Section: Fouling Types and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research findings indicate that both pore narrowing and pore blockage initiate the buildup of a cake/gel layer on the membrane surface [61,62,63,64,65]. Pore narrowing and pore blockage are considered irreversible and a formation of gel/cake layer primarily reversible [66,67]. For example, Zhang et al 190 [68] found that the absorption of low and high MW hydrophilic compounds led to irreversible membrane fouling; due to their hydrophilicity, these fractions are not restricted from entering the membrane pore.…”
Section: Fouling Types and Mechanismsmentioning
confidence: 99%
“…The configuration of UF units also affected the propensity of fouling [377,378]. To shed light on the effect of filtration mode on total fouling behavior, Chang et al [66] found that the total fouling of an HA and SA solution under constant pressure filtration compared to, or was slightly higher than under constant flux filtration. Ye et al [377] found that increasing the duration of filtration from 20 minutes to 60 minutes did not increase the percentage of reversible fouling that could be removed via backwashing; increasing the filtration period from 60 minutes to 90 minutes further exacerbated irreversible fouling; while expanding the backwash duration from 10 to 30 sec-1275 onds, decreased the initial transmembrane pressure at the beginning of the following filtration cycle and fouling rate by over 50% [377].…”
Section: Physical Membrane Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of transmembrane pressure on pure water and rinsing water fluxes under UF alone and hybrid adsorption/UF system. remove and might require chemical cleaning [89][90][91]. The efficiency of the membrane regeneration was determined by checking the water permeability.…”
Section: Membrane Regenerationmentioning
confidence: 99%
“…Other methods of water treatment techniques include reverse osmosis, chemical precipitation, catalytic reduction, ion exchange, electrodialysis and membrane filtration. However, most of these methods are practically expensive, result in the wastage of water, are singly less efficient, are highly specific and have the problem of membrane fouling [ 29 , 30 , 31 , 32 , 33 ]. The development of an all-inclusive water detoxifier is a major challenge in the water industry.…”
Section: Introductionmentioning
confidence: 99%